Impact of a knowledge commons on collaborative consumption : an ethnographic study. - Nur Syahidah Alim. (2012)
This dissertation explores the impact of the knowledge commons on Collaborative Consumption, with a special focus on collaborative lifestyles (i.e. coworking spaces) in Singapore. It also attempts to investigate and address three research questions: (1) What are the knowledge dynamics in the “knowledge commons”? (2) How may the knowledge dynamics identified be harnessed to support collaborative lifestyles (i.e. one of the three systems of Collaborative Consumption)? (3) Under what conditions are these knowledge dynamics sustainable? To pursue this objective, the research begins by realising the utmost importance for knowledge commons to master the capabilities in defining and managing its current knowledge assets. A conceptual framework is hence proposed, incorporating four-stages process to further refine knowledge assets into key value drivers. These four stages are: (1) diagnosis of knowledge assets, (2) formulation of strategies, (3) launch of new Collaborative Consumption activities, and (4) evaluation of performance. The second phase of the research involves an ethnographic study of two local knowledge commons – KENNEL and Founders HQ. The findings are analysed using a combination of Comprehensive Intellectual Capital Management (CICM) frameworks, knowledge audits and knowledge flow models. From the research, it may be concluded that, even by applying a set of conditions and practices that harness and sustain knowledge dynamics, the knowledge commons must still ensure that its current strategies are well-defined and provide a harmonious fit with the different key aspects and values drivers. This becomes a basis for attaining long-term success and sustainable competitive advantage.